2015
DOI: 10.1212/wnl.0000000000001462
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of fingolimod in multiple sclerosis

Abstract: Objective:To assess long-term safety and efficacy of fingolimod in patients with relapsing-remitting multiple sclerosis (RRMS).Methods:Patients completing FTY720 Research Evaluating Effects of Daily Oral Therapy in MS (FREEDOMS) were eligible for this dose-blinded, parallel-group extension study, continuing fingolimod 0.5 mg/day or 1.25 mg/day, or switching from placebo to either dose, randomized 1:1. Efficacy variables included annualized relapse rate (ARR), brain volume loss (BVL), and confirmed disability p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
141
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 10 publications
24
141
4
4
Order By: Relevance
“…These studies found no further increased risk of FAME over a period of up to 4.5 years. 2,31 In a retrospective study by Ontaneda et al, 32 a similar incidence (3/317, 0.9%) of macular oedema at 3 months after therapy initiation was reported.…”
Section: Fingolimod and The Eyementioning
confidence: 65%
See 2 more Smart Citations
“…These studies found no further increased risk of FAME over a period of up to 4.5 years. 2,31 In a retrospective study by Ontaneda et al, 32 a similar incidence (3/317, 0.9%) of macular oedema at 3 months after therapy initiation was reported.…”
Section: Fingolimod and The Eyementioning
confidence: 65%
“…In vivo, fingolimod is phosphorylated to fingolimodphosphate and becomes structurally similar to a sphingolipid called sphingosine-1-phosphate (S1P), an extracellular mediator, preventing it from binding normally to the five types of S1P receptors (S1PR [1][2][3][4][5]. At the cellular level, it leads to internalisation and eventual degradation of these cell surface receptors and abnormal cellular function and communication.…”
Section: Fingolimod's Mode Of Action and Its Cardiovascular Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…fingolimod, amitryptiline) (Nahrlich et al, 2013;Kappos et al, 2015). Sphingolipid metabolic rate is enhanced in early pregnancy in the first inflammatory implantation phase (Kaneko-Tarui et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Phase III, controlled clinical studies with large sample sizes and more than 1000 patients with RRMS demonstrated that fingolimod significantly reduced annualized relapse rates, MRI measures, and brain volume loss compared with placebo and IM interferon -β1a and that its beneficial properties were retained in long-term extension studies (11,12,13,14,15,16).…”
Section: Discussionmentioning
confidence: 99%